The Implementation of Good Corporate Governance Principles in Budget Management at BKKBN Provincial Representative Office in Bali - Ida Ayu Lidya Primadona; I Nyoman Kusuma Adnyana; I Putu Mega Juli Semara Putra (Greenation Research & Yayasan Global Resarch National, 2025)
Budget management encompasses a series of financial regulatory activities, including planning, bookkeeping, expenditure, supervision, and financial accountability within an organization or institution. This study employs a qualitative research approach to explore the extent to which Good Corporate Governance (GCG) principles are implemented in budget management at the Provincial Representative Office of BKKBN Bali. The findings reveal that all GCG principles—transparency, accountability, responsibility, independence, and fairness—have been applied by both budget managers and users. Nevertheless, several challenges remain, such as the low realization of the Special Allocation Fund (DAK) for the Family Planning sub-sector and limited support from regional (district/municipal) government budgets (APBD). As a solution, cross-sectoral synergy and the strengthening of ethical organizational commitment are necessary. The implementation of GCG has been proven to foster a more harmonious, transparent, and sustainable approach to budget governance.